Comorbidity of dementia and age-related macular degeneration calls for clinical awareness: a meta-analysis. Issue 12 (18th April 2019) - Rong, Shi Song; Lee, Bo Yee; Kuk, Andrew K; Yu, Xin Ting; Li, Suki S; Li, Jian; Guo, Yanjun; Yin, Yilin; Osterbur, David L; Yam, Jason C S; Cheung, Carol Y; Chen, Li Jia; et al.
Abstract : Aim: To determine the association between dementia and age-related macular degeneration (AMD) using meta-analysis. Methods: We searched in the MEDLINE, EMBASE, Web of Knowledge, PsycInfo and Cochrane database of systematic reviews for studies published from March 1959 to March 2018. We included cross-sectional, case–control and cohort studies that evaluated the association of dementia/Alzheimer's disease (AD) with AMD (as outcome) and the association of AMD with dementia/AD (as outcome). Studies that compared cognitive functions between AMD and controls were also included. The summary outcomes, namely odds ratio (OR), relative risk, mean differences and corresponding 95% CIs, were estimated using random effects models. We performed sensitivity analysis based on study quality and individual study effect to control for potential biases. Results: Among 2159 citation records, we identified 21 studies consisting of 7 876 499 study subjects for meta-analysis. Patients with dementia (padjusted ≤0.017, OR≥1.24, I 2 ≤9%) or AD (p=0.001, ORunadjusted =2.22, I 2 =50%) were at risk for AMD, particularly for late AMD (padjusted <0.001, OR=1.37, I 2 =0). AMD was also significantly associated with increased risk of AD/cognitive impairment (padjusted =0.037, OR=2.42, I 2 =38%). Moreover, patients with AMD had poorer cognitive functions when compared with controls, including Mini-Mental State Examination (p<0.001, I 2 ≤79%) and Trail Making Test A (p<0.001, I 2 =0). Sensitivity analysis and Egger's test indicated our results were less likely biased. Conclusions: A significant association between dementia/AD and AMD calls for greater clinical awareness. The cost-effectiveness of routine screening for the other condition in patients with primary diagnosis of dementia/AD or AMD requires further study.